(untitled) (Archives of Clinical Psychiatry, 2015)
Background Bipolar disorder is a chronic condition that affects the functioning of its carriers in many different ways, even when treated properly. Therefore, it’s also important to identify the psychosocial aspects that could contribute to an improvement of this population’s quality of life.Objective Carry out a literature review on the role of social support in cases of bipolar disorder.Method A research on the following online databases PubMed, Lilacs and SciELO was conducted by using the keywords “social support” or “social networks” and “mood disorders” or “bipolar disorder” or “affective disorder,” with no defined timeline.Results Only 13 studies concerning the topic of social support and BD were found in the search for related articles. Generally speaking, the results show low rates of social support for BD patients.Discussion Despite the growing interest in the overall functioning of patients with bipolar disorder, studies on social support are still rare. Besides, the existing studies on the subject use different methodologies, making it difficult to establish data comparisons.